Analisis Merger Bank Syari’ah Indonesia (BSI) Dalam Perkembangan Perbankan Syari’ah Di Indonesia - Qibtiyah, Mariyatul; Wicaksono, Fitra (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
Research entitled "Analysis of the Merger of Indonesian Syari'ah Bank (BSI) in the Development of Syari’ah Banking in Indonesia" is motivated by the proliferation of news on television, social media, advertisements, and socialization carried out by related banks. This reason makes the author interested in conducting Research on the merger of Indonesian state-owned Syari’ah banks. The merger of the state-owned Syari’ah banks consists of BRI Syariah, Mandiri Syariah Bank, and BNI Syari'ah, while the Government as the owner. Through the Ministry of SOEs represented by SOE Minister Erick Thohir has initiated the merger of Syari’ah banks under his Ministry since 2020 by actively coordinating with related institutions.  On February 1, 2021 the merged bank can be inaugurated and start operating under a new name, namely Bank Syari'ah Indonesia (BSI). Besides this study aims to find out more in depth whether the merger have a positive impact on the development of Syari’ah banking in Indonesia. From the results of the author's analysis of the performance achievements of BSI and also the performance achievements of Syari’ah banking in Indonesia, it is proven that it can improve the performance of Syari’ah banking. Specifically, the improvement can be seen in terms of assets, CAR, ROA, financing, profitability, efficiency, additional office networks and number of employees, while reducing NPF and BOPO. Therefore, it can be concluded that the merger of Bank Syariah Indonesia (BSI) has made a positive contribution to the development of Syari’ah banking in Indonesia, and especially for Bank Syari'ah Indonesia (BSI) itself.